Buzhongyiqi Decoction Protects Against Loperamide-Induced Constipation by Regulating the Arachidonic Acid Pathway in Rats - Ju, Wan-Jun; Zhao, Ze-kuo; Chen, Shao-Li; Zhou, Dan-dan; Yang, Wen-Ning; Wen, Xiao-Ping; Du, Guang-Li (Frontiers in Pharmacology, 2020)
Constipation is a common gastrointestinal disorder without effective treatment approach. Buzhongyiqi decoction (BZYQD) is a classical formula that has been commonly used for gastrointestinal disorders for nearly 1,000 years. In this study, we aimed to investigate the protective effect of BZYQD against loperamide-induced constipation and its potential mechanism. Rats with loperamide-induced constipation were orally administered BZYQD. BZYQD treatment obviously increased the small intestinal transit rate and alleviated colon tissue pathological damage. Subsequently, serum metabolomics study was performed to identify the metabolites affected by BZYQD. Metabolomics identified that the levels of 17 serum metabolites, including prostaglandin E2 (PGE2), arachidonic acid (AA), and inositol, were significantly changed in BZYQD-treated group compared with those in the loperamide-induced group. Pathway analysis revealed that those metabolites were mainly associated with arachidonic acid metabolism, biosynthesis of unsaturated fatty acids, ascorbate and aldarate metabolism, inositol phosphate metabolism. Additionally, BZYQD treatment down-regulated the cyclooxygenase-2 expression and decrease production of the proinflammatory mediator PGE2. Further study revealed that BZYQD administration decreased serum levels of the inflammatory factors IL-1β and TNF-α, inhibited phosphorylation of the nuclear transcription factor NF-κB, and down-regulated expression of the inflammatory factors IL-1β and IL-6 in the constipated rat colon. Moreover, BZYQD treatment also increased serum levels of inositol, motilin and gastrin, and promoted gastrointestinal motility. In conclusion, the present study suggested that BZYQD exerted a protective effect against loperamide-induced constipation, which may be associated with its role in regulation of multiple metabolic pathways.